ANALISIS INDIKATOR DINAMIS KESEIMBANGAN PENDUDUK DENGAN DAYA DUKUNG DAN DAYA TAMPUNG LINGKUNGAN DI PROVINSI JAWA TENGAH - Woyanti, Nenik (VALUE ADDED | MAJALAH EKONOMI DAN BISNIS, 2009)
Most of environment problems happen because of population behaviour was not environment friendly. Human quality and equalibrium environment can be known from interracting between people and environment, and factors which influence them. This study used 3 components, namely: human resources (f.e. Total Fertility Rate, Infant Mortality Rate), economy (Gross Domestic Product), and social (f.e. education). It needed secondary data and be digested with the deviasi standart measurement. And then, the data were be analysed by the descriptive analysis. The conclusion were: TFR anda IMR in Central of Java was good category because of its value were in range target. GDP in Central of Java was middle category because of even it increased but it was still under the target value, and lower than national value; the educated-people proportion was good category because of its value was in range target. The local government should press TFR and IMR in Central of Java until smaller than 2 percent through using persuative approach to reproductive couples, through increasing health and education services facilities; through expanding field of endeavour. Key Words: population, environtment, equilibrium, TFR, IMR, GDP, educated-people